Keseimbangan Badan dan Jiwa Perspektif Abu Zaid Al-Balkhi - Musfihin Musfihin (Jurnal Studia Insania, 2019)
Abu Zaid al-Balkhi was a multi-talent scientist in 9th-century Islam in several fields, his ability to write two themes in a systematic work had brought him to be known as the first mental health pioneer who before that time prioritized physical health. The purpose of this study is to describe the concept of Body and Soul according to Abu Zaid al-Balkhi, using the Research Library method from the data of Abu Zaid al-Balkhi's work entitled "Mashalih al-Abdan wal-Anfus" and from other sources related to research. This study found 2 (two) topics, among others: 1. The importance of maintaining body and soul health, namely body health as in general principles of health science such as maintaining environmental health, shelter, water, and air sanitation, while for mental health the importance of preserving mind and feelings, 2. Differentiation of treatment/treatment in dealing with neurosis and psychosis disorders, for neurotic disorders the therapeutic process is carried out with cognitive therapy while for psychosis disorders the therapeutic process is done spiritually, thus the importance of maintaining a balance of body and soul for health, otherwise imbalance will cause disease.